Actuarial neutrality across generations applied to public pensions under population ageing: effects on government finances and national saving - Oksanen, Heikki; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2005)
In welfare states, collective saving has declined to a persistently negative level, while reduced fertility and increasing longevity are leading to increasing pension liabilities. Actuarial neutrality across generations is presented as a benchmark for designing pension reforms to meet the challenges of population ageing. It is shown that this condition can be respected by a wide range of pension reforms, with very different consequences for public finance target setting. The rules for public pensions in national accounting are also discussed. Finally, the combined effects of population ageing and public pension rules on national saving are discussed.
Economic Papers